2008
DOI: 10.4028/www.scientific.net/amr.44-46.253
|View full text |Cite
|
Sign up to set email alerts
|

Research on Tolerance Analysis System Based on 3D Collaborative Design Platform

Abstract: Computer supported collaborative work (CSCW) technology is used to solve the resource-sharing problems in collaborative design, analysis, and manufacture. To address this need, a system called CollabVue for collaborative product design between designers and manufacturers is proposed in this study. This paper first introduces the framework of tolerance analysis system based on CollabVue, and then discusses the utilization of geometric topology information in 3D model to resolve the problem of dimension informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Tolerance plays a significant role on the function, cost, assembly, and quality of products. Substantial studies of the tolerance analysis and synthesis have been conducted (Singh et al, 2005;Shen et al, 2008;Shao et al, 2008). Whitney (2008) found that some designs required tight tolerances on the over-constrained degrees of freedom and most tolerance analysis software did not test designs for their state of constraint and might yield incorrect answers.…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance plays a significant role on the function, cost, assembly, and quality of products. Substantial studies of the tolerance analysis and synthesis have been conducted (Singh et al, 2005;Shen et al, 2008;Shao et al, 2008). Whitney (2008) found that some designs required tight tolerances on the over-constrained degrees of freedom and most tolerance analysis software did not test designs for their state of constraint and might yield incorrect answers.…”
Section: Introductionmentioning
confidence: 99%